Provider-reported acceptance and use of the Centers for Disease Control and Prevention messages and materials to support HPV vaccine recommendation for adolescent males. Issue 35 (29th July 2016) - Scherr, C.L.; Augusto, B.; Ali, K.; Malo, T.L.; Vadaparampil, S.T.
Highlights: CDC has messages and materials to support physicians' HPV vaccine recommendations. Many physicians were unaware of the CDC's resources, suggesting suboptimal reach. Most physicians reported favorable views of the CDC's messages. Physicians requested additional information about HPV vaccine safety and efficacy. Abstract: Purpose: We evaluated Florida-based physicians' awareness and use of the Centers for Disease Control and Prevention's (CDC) "You are the Key" campaign website, including messages to support physicians' human papillomavirus (HPV) vaccine recommendations. Methods: Using closed-ended and free-text survey items, physicians' ( n = 355) practices related to HPV vaccination recommendations for males and use of the CDC's materials were assessed. Descriptive statistics were calculated for closed-ended questions, and thematic analysis was conducted on free-text responses. Results: Over half of physicians were aware of the CDC's website ( n = 186; 57.9%); of those aware, fewer than half reported using the website ( n = 86; 46.2%). Slightly more than half reported awareness of the CDC's messages ( n = 178; 55.3%); however, less than one-third of those aware reported using them ( n = 56; 31.5%). Physicians' comments on the CDC's messages were favorable; 78.6–93.2% said they would use a message in clinic. Conclusion: Additional research is needed to identify the best mechanisms for resource dissemination and to understand why physicians do not use these messages, despite favorable attitudes.